PERAN KEPOLISIAN DALAM MENEGAKKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PENIPUAN ONLINE MELALUI MEDIA SOSIAL INSTAGRAM DI POLSEK BEKASI UTARA - Gresia, Gresia; Chandra Aritonang; Armunanto Hutahaean (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
Online fraud refers to a crime where network system and computer can beused as the facility or to do the crime. It is an activity that is against the law and is done by cartain people who are responsible for the crime. It can be done via internet and may involve purchase fraud, transaction fraud and data theft, where computer can be used (e-commerce) to cary out the action. The factors that my cause the online froud phenomenom include society factor, cultura factor and environmental faktor. From various online fraud crimes that have happened, the Departmental Resort Police (Polsek) of Bekasi has attepted a number of efforts, including of prosecuting the criminal, tracking the location of the perpetrator, blocking the bank account of the perpetrator, supporting various institutions related to the criminal act, as well as on there forts including addressing thr issue and making it public trough the internet.